Longitudinal Evaluation of the InaRISK Disaster Information System using the Public Satisfaction Index - Findi Ayu Sariasih (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2026)
This study aims to evaluate public satisfaction with the InaRISK application as a national disaster risk information system developed by the National Disaster Management Agency (BNPB). The research is a continuation of a previous study using the same measurement instrument, enabling a longitudinal comparison of service quality. The study applies the Public Satisfaction Index (Indeks Kepuasan Masyarakat/IKM) method based on the Regulation of the Ministry of Administrative and Bureaucratic Reform Number 14 of 2017, which measures nine service elements. Data were collected through an online questionnaire distributed via Google Forms to 2,448 respondents who participated in the InaRISK application socialization webinar in 2025. The results show that the Public Satisfaction Index in 2025 reached 84.54, categorized as “Good”, which indicates an improvement compared to the previous study that obtained a score of 83.46. Among the evaluated service elements, service procedures obtained the highest score and was categorized as “Very Good”, while response speed remained in the “Less Good” category. These findings indicate that the overall quality of InaRISK digital services has improved, although improvements in service responsiveness are still necessary to enhance user satisfaction more evenly. This study contributes to the evaluation of digital public services in disaster management systems through a longitudinal measurement approach.